2006
DOI: 10.1002/chin.200623028
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Complex‐Catalyzed [2 + 2 + 2] Cycloaddition of α,ω‐Diynes with Monoynes and Monoenes.

Abstract: Cycloaddition reactions O 0070Iridium Complex-Catalyzed [2 + 2 + 2] Cycloaddition of α,ω-Diynes with Monoynes and Monoenes. -A detailed account on the recently published Ir-catalyzed cycloaddition of diynes with monoalkynes is presented and extended by monoalkenes as addition partners. In some of the reactions using monoalkenes, a novel aromatization of initial formed cyclohexadiene derivatives is observed. A ligand-controlled switch in regioselectivity is discovered in the reactions of 1,6-octadiene derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…To study the substrate scope of A-15 mediated Knoevenagel condensation, substituted 5 and 6 were reacted in toluene to afford diversified 4 by the optimal conditions established (Table 1, entry 16). As shown in Table 2, the facile formation of 4a−4ai showed that the R and Ar′ substituents of 5a−5p and the Ar substituent of 6a−6y did not influence the yield (entries 1−41).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the substrate scope of A-15 mediated Knoevenagel condensation, substituted 5 and 6 were reacted in toluene to afford diversified 4 by the optimal conditions established (Table 1, entry 16). As shown in Table 2, the facile formation of 4a−4ai showed that the R and Ar′ substituents of 5a−5p and the Ar substituent of 6a−6y did not influence the yield (entries 1−41).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the incorporation of the sulfonyl group into organic molecules is an important task. 21−27 In Scheme 1, the typical routes for the synthesis of 2-sulfonyl indanes and indenes include: (i) oxidation of 2-indanyl phenyl sulfide, 15 (ii) Ir + catalyzed [2 + 2 + 2] cycloaddition of sulfonyl diyne and monoyne, 16 (iii) base-mediated conjugation of tosylmethyl isocyanide (TosMIC) and 2-bromobenzyl bromide, 17 (iv) Cu + promoted sulfonylation of indene with dimethyl sulfoxide in the presence of an oxygen atmosphere, 18 (v) Pd 2+ promoted remote ortho C−H alkenylation of arylethyl 2-pyridyl sulfone followed by base mediated intramolecular ring-closure, 19 and (vi) electrooxidative tandem cyclization of activated alkynes with sulfinic acid. 20 Although diversified routes have been described to construct sulfonyl indanes or indenes, it still remains challenging to explore a facile and highyield method in the formation of this core system.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations